Legal review of the General provisions of the Junta de Andalucía - Guichot Reina, Emilio (Revista Andaluza de Administración Pública, 2017)
Se recogen y comentan las disposiciones generales más relevantes de la Junta de Andalucía publicadas en el BOJA en el primer cuatrimestre de 2017 (enero-abril).The most relevant general provisions of the Junta de Andalucía published in the BOJA (Official Journal of t